A New Anionic Oxalamide Lauryl Succinate Sodium Sulfonate Gemini Surfactant: Microwave‐Assisted Synthesis and Surface Activities. Issue 5 (3rd April 2014) - Chen, Hong; Zhu, Baowei
Abstract: An anionic Gemini surfactant, oxalamide lauryl succinate sodium sulfonate, was synthesized successfully through amidation, esterification and sulfonation reactions under microwave irradiation conditions by using maleic anhydride, ethylenediamine, lauryl alcohol, sodium sulfite as the starting materials. The best reaction conditions for synthesize the target product were obtained by single factor and orthogonal optimization methods. FTIR, elemental analysis and 1 H‐NMR analysis were used to confirm the chemical structure of the surfactant. The critical micelle concentration (CMC) in aqueous solution, surface tension, emulsification capacity and foaming power were determined. The critical micelle concentration and γ CMC are respectively equal to 3.5 × 10 −4 mol L −1 and 21.5 mN m −1 . It was found that microwave‐assisted synthesis is an efficient means of preparation of this anionic Gemini surfactant with shorter times and higher yields.